Soil Organic Matter and Root and Rhizome Responses to Management Strategies in Smooth Bromegrass Pastures. (1st September 2014) - Guretzky, John A.; Wingeyer, Ana B.; Schacht, Walter H.; Klopfenstein, Terry J.; Watson, Andrea
Abstract : Soil organic matter (SOM) is a key component of pasture production. This study investigated how management strategies that varied amount and form of N input in a long‐term experiment affected concentrations and stocks of total‐soil organic C and N, particulate organic carbon (POC), particulate organic nitrogen (PON), root and rhizome mass, C and N contents in topsoil of smooth bromegrass ( Bromus inermis Leyss.) pastures with silty clay loam soils in a wet (2010) and dry (2012) year. Management strategies included: (i) unfertilized pasture grazed with unsupplemented beef cattle (CONT); (ii) unfertilized pasture grazed with dried distillers grains plus solubles (DDGS)‐supplemented beef cattle (SUPP); and (iii) nitrogen‐fertilized pasture grazed with unsupplemented beef cattle (FERT). After 8 yr, management strategies had similar concentrations and stocks of total‐soil organic C and N, POC, and PON, and there were no management strategy × year interactions. From 2010 to 2012, total‐soil organic C and N, POC, and PON stocks increased as soils dried and soil bulk density increased. The CONT and SUPP management strategies had less root and rhizome mass (concentrations and stocks) and greater soil bulk density than FERT. These belowground responses were consistent with earlier research conducted at the site demonstrating greater herbage accumulation and litter deposition in FERT. Management strategies that vary amount and form of N inputs into pasture appear to have low potential to affect total‐soil organic C and N concentrations in the short‐term, but long‐term effects of less root and rhizome contents remain unknown.